KAJIAN YURIDIS TERHADAP UNSUR KEALPAAN DALAM PASAL 310 AYAT (4) UNDANG-UNDANG NO. 22 TAHUN 2009 TENTANG LALU-LINTAS DAN ANGKUTAN JALAN PADA TINGKAT PENYIDIKAN DI POLRES WONOGIRI - HARTA, AD BANK (Dinamika Hukum, 2019)
The purpose of this study is to examine the disclosure of elements of negligence in the crime of traffic accidents and assess the obstacles at the investigation level, especially at the Polres Wonogiri. The background of the research is that the element of neglect in the crime of a traffic accident is a very important element. Disclosure of elements of negligence requires adequate knowledge and understanding from the investigator. The element of negligence is an essential element in the formulation of criminal acts of traffic accidents. Therefore this study will examine how investigators uncover elements of negligence in criminal acts of traffic accidents. The research method consists of the type of research is normative juridical which is equipped with empirical data through observation. The nature of the research is descriptive. The research material consists of primary legal material, namely Law No. 8 of 1981 concerning the Criminal Procedure Code, Law No. 22 of 2009 concerning Road Traffic and Transportation, REGULATION OF KAPOLRI No. 15 of 2013 concerning Procedures for Handling Traffic Accidents. Secondary Legal Materials consist of Government Regulation No. 27 of 1983, Resume of Cases of Traffic Accident Crimes. The tertiary legal material is the Law Dictionary. The method of data collection is done by literature study and observation. The method of data analysis is done qualitatively. Research Results are elements of negligence in the crime of traffic accidents since the investigation level must be proven by the investigator. Investigation efforts to uncover elements of negligence must be based on sufficient evidence such as testimony of witnesses, experts, letters, instructions and statements of the defendant. Constraints in the disclosure of elements of negligence in the crime of traffic accidents are evidence in the Case Event Place that has been damaged or lost. Witnesses who knew directly about the incident did not exist. Most people who gather at the Case Events are people who give help to victims. They are not people who know, hear and see directly the events. Another obstacle is the weather conditions such as rain, the state of the Case Event without lighting. Internal constraints are the number of Human Resources that still need to be improved both in quality and quantity. Keywords: Juridical Study, Elements of Forgiveness, Investigation, Traffic Accident Crimes, Wonogiri Police Station.